Faktor-Faktor yang Mempengaruhi Pengungkapan Corporate Social Responbility (CSR) pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) tahun 2012-2015 dengan Menggunakan Islamic Social Reporting (ISR) Index sebagai Tolok Ukur - Novrizal, Muhammad Fajrul; Fitri, Meutia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
Islamic Social Responbility (ISR) is an index of social responsibility disclosure (CSR) that has specific indicator on the ethical principles of Islam. In this study, assessment a level of CSR disclosure conducted on companies in the Jakarta Islamic Index (JII). This study aim to obtain an empirical evidence about the analysis of the factors that affect the disclosure of Corporate Social Responsibility (CSR). Factors used include profitability, types of industry, environmental performance and the size of the company. Measurement of Corporate Social Responsibility (CSR) is based on the category of Islamic Social Reporting (ISR) that used to calculate the Islamic Social Reporting index as seen from the companys annual report. This research is a quantitative research. The population of this research is all companies that listed in Jakarta Islamic Index totaling 30 companies sharia. The sampling technique used is Purposive sampling. The total sample is 16 companies sharia. Analysis of the data used to test classic assumptions and hypothesis testing with multiple regression method. The results of this study indicate that the environmental performance and the size of the company have a significant effect on the disclosure of Islamic Social Responbility. While profitability and industry type does not significantly affect the disclosure of Islamic Social Responbility in Indonesia.Keywords: Islamic Social Reporting, Corporate Social Responsibility, Jakarta Islamic Index, profitability, types of industry, environmental performance and the size of the company.